Ensayo de enraizamiento de estaquillas del alcornoque (Quercus suber L.) - Ribeiro, M M A (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
An experiment was made in order to study the tooting process in cuttings of young cork oaks. Different treatments with indol butiric acid (IBA) in different concentrations, two different origins of the cutting (basal and apical) and two different base of the cutting treatements (with or without bark removal) were performed. The best performances were achieved with 0.5% and 1 % of IBA (not significatively different) with 54 and 52 % of rooting, respectivly, after 3 months. The first treatment not only produces more roots by cutting but longer ones as well. Bark removal has the same effect but it does not improve rooting. The origin of the cutting had no influence in the studied parameters.
Keywords: Cork oak; Cuttings; Quercus suber L.; rooting; vegetative propagation